Reliability and magnitude of loaded countermovement jump performance variables: a technical examination of the jump threshold initiation - Pérez-Castilla, A.; Rojas, F. J.; García-Ramos, A. (Sports Biomechanics, 2022)
Different thresholds have been used to determine the start of the force-time analysis during countermovement jump testing. This study examined the influence of the jump starting threshold on the reliability and magnitude of loaded countermovement jump (CMJ) performance variables. Seventeen males were tested during two sessions using five loading conditions (17-30-45-60-75 kg). The CMJ performance was analysed with a force platform. The initiation of the eccentric phase was defined as the first instant in which the vertical ground reaction force was below system weight by 10 N, 50 N, 1% of system weight (1%SW), 10% of system weight (10%SW) and five standard deviations of system weight minus 30 ms (5SDSW). The 50 N, 10%SW and 5SDSW provided a higher reliability for the mean values of velocity and power as well as for the temporal variables only during the eccentric phase compared to the 10 N and 1%SW threshold (CV ratio>1.15). The magnitude of several variables collected during both phases for the 50 N, 10%SW and 5SDSW thresholds significantly differed with respect to 10 N and 1%SW thresholds (p< 0.05). These results suggest that the jump starting threshold may influence both the reliability and magnitude of loaded CMJ performance variables, especially during the eccentric phase.